A profile shape correction to reduce the vertical sensitivity of cosmic‐ray neutron sensing of soil moisture. Issue 1 (5th November 2020) - Scheiffele, Lena M.; Baroni, Gabriele; Franz, Trenton E.; Jakobi, Jannis; Oswald, Sascha E.
Abstract: In recent years, cosmic‐ray neutron sensing (CRNS) has shown a large potential among proximal sensing techniques to monitor soil moisture noninvasively, with high frequency and a large support volume (radius up to 240 m and sensing depth up to 80 cm). This signal is, however, more sensitive to closer distances and shallower depths. Inherently, CRNS‐derived soil moisture is a spatially weighted value, different from an average soil moisture as retrieved by a sensor network. In this study, we systematically test a new profile shape correction on CRNS‐derived soil moisture, based on additional soil moisture profile measurements and vertical unweighting, which is especially relevant during pronounced wetting or drying fronts. The analyses are conducted with data collected at four contrasting field sites, each equipped with a CRNS probe and a distributed soil moisture sensor network. After applying the profile shape correction on CRNS‐derived soil moisture, it is compared with the sensor network average. Results show that the influence of the vertical sensitivity of CRNS on integral soil moisture values is successfully reduced. One to three properly located profile measurements within the CRNS support volume improve the performance. For the four investigated field sites, the RMSE decreased 11–53% when only one profile location was considered. We therefore recommend to install along with a CRNS at least one soil moisture profile in a radial distance <100 m and a measurement depth down to 50 cm. Profile‐shape‐corrected, CRNS‐derived soil moisture is an unweighted integral soil moisture over the support volume, which is easier to interpret and easier to use for further applications. Core Ideas: Soil moisture derived from cosmic‐ray neutron sensing is inherently weighted. Few additional soil moisture profile measurements should complement the method. A profile shape correction unweights cosmic‐ray‐derived soil moisture. Corrected cosmic‐ray soil moisture is a better integral average of the support volume.